Crustacea in Arctic and Antarctic Sea Ice: Distribution, Diet and Life History Strategies - Arndt, Carolin E.; Swadling, Kerrie M. (Advances in Marine Biology, 2006)
This review concerns crustaceans that associate with sea ice. Particular emphasis is placed on comparing and contrasting the Arctic and Antarctic sea ice habitats, and the subsequent influence of these environments on the life history strategies of the crustacean fauna. Sea ice is the dominant feature of both polar marine ecosystems, playing a central role in physical processes and providing an essential habitat for organisms ranging in size from viruses to whales. Similarities between the Arctic and Antarctic marine ecosystems include variable cover of sea ice over an annual cycle, a light regimen that can extend from months of total darkness to months of continuous light and a pronounced seasonality in primary production. Although there are many similarities, there are also major differences between the two regions: The Antarctic experiences greater seasonal change in its sea ice extent, much of the ice is over very deep water and more than 80% breaks out each year. In contrast, Arctic sea ice often covers comparatively shallow water, doubles in its extent on an annual cycle and the ice may persist for several decades. Crustaceans, particularly copepods and amphipods, are abundant in the sea ice zone at both poles, either living within the brine channel system of the ice‐crystal matrix or inhabiting the ice–water interface. Many species associate with ice for only a part of their life cycle, while others appear entirely dependent upon it for reproduction and development. Although similarities exist between the two faunas, many differences are emerging. Most notable are the much higher abundance and biomass of Antarctic copepods, the dominance of the Antarctic sea ice copepod fauna by calanoids, the high euphausiid biomass in Southern Ocean waters and the lack of any species that appear fully dependent on the ice. In the Arctic, the ice‐associated fauna is dominated by amphipods. Calanoid copepods are not tightly associated with the ice, while harpacticoids and cyclopoids are abundant. Euphausiids are nearly absent from the high Arctic. Life history strategies are variable, although reproductive cycles and life spans are generally longer than those for temperate congeners. Species at both poles tend to be opportunistic feeders and periods of diapause or other reductions in metabolic expenditure are not uncommon.
Keywords: Sørishavet; copepoder; crustacea; havis; krill; marin biologi; plankton; polarområdene; sjøis

A review of bipolarity concepts: history and examples from Radiolaria and Medusozoa (Cnidaria) - Stepanjants, Sofia D; Cortese, Giuseppe; Kruglikova, Svetlana Borisovna; Bjørklund, Kjell R (Marine Biology Research, 2006)
Bipolarity, its history and general interpretation are investigated and discussed herein. Apart from the classical view, namely that a bipolar distribution is a peculiar biogeographical phenomenon, we propose that it is ecologically controlled too. This approach was used for bipolarity assessment within the following groups: Phaeodaria, Nassellaria, Spumellaria (Radiolaria) and Medusozoa (Cnidaria). We recognize 46 bipolar radiolarian species and three radiolarian genera. However, although species concepts in radiolarians are relatively stable and well known, the high-rank taxonomy of radiolarians is still not well defined. Caution should therefore be taken in the interpretation of distribution data at a taxonomic level higher than the species. In the Medusozoa, bipolarity is observed for 23 species and 32 genera. The different ways in which bipolarity can develop are discussed under the different groups, but preference has been given to the recent and most probable routes of migration. In our investigation of the bipolarity phenomenon, we reviewed more than 400 articles dealing with taxonomy, ecology and biogeography of the modern fauna in both groups.
Keywords: Sørishavet; marinbiologi; migrasjon; nesledyr; plankton; økologi